Daily Activity of Teuku Umar University Students Going to Campus - firzan firzan; Irfan Irfan; Samsunan Samsunan; Rahmat Djamaluddin; Deni Ilham Yani (International Journal of Engineering, Science and Information Technology, 2023)
Teuku Umar University (UTU) is a public university located in West Aceh Regency. The number of active students at UTU was recorded as 6,636 in the academic year 2021-2022. Currently, the UTU campus lacks public transportation serving its vicinity. This study aims to identify the daily activities of UTU students in commuting to the campus and to determine the extent of students' response to the implementation of public transportation services within a Â±5 KM buffer zone from the UTU campus. This research utilizes two types of data analysis methods, namely qualitative descriptive and quantitative descriptive. The research findings indicate that 93.5% of students strongly agree with the concept of implementing public transportation, and 75.3% of students agree to switch from private vehicles to public transportation. The majority of daily travel activities are conducted by female students, accounting for 54% compared to 46% of male students. The modes of transportation used to reach the campus are motorcycles (56%), bicycles (6%), and walking (38%). Regarding the frequency of departure times to the campus, 41% of students depart at 08:00 AM, 23% at 09:40 AM, 15% at 10:30 AM, 12% at 11:20 AM, 6% at 01:50 PM, and 3% depart at 04:20 PM. As for the frequency of return times, 16% return at 01:30 PM, 21% at 11:20 AM, 34% at 01:50 PM, 10% at 03:30 PM, 16% at 04:20 PM, and 3% return at 05:10 PM. Based on this study, we recommend developing a dedicated public transportation service concept for UTU students. Data on students' daily activities can serve as crucial input for the future development of public transportation projects.